Designing Elite Recruitment Model for Iranian Educational organizations - moghimi, Zahra; Memarzadeh Tehran, Gholamreza; Alborzi, Mahmoud (Iranian Journal of Educational Sociology, 2022)
Purpose: The current research proposes a model for elite’s recruitment to Iranian educational organizations based on the ethics and specific cultural contexts of Iranian society.Methodology: This is a combination of two quantitative and qualitative approaches. This is also an applied descriptive-exploratory paper. The primary pattern of research is extracted from the theoretical background and consists of four dimensions (competencies definition, effective factors analysis, competitor’s analysis, and recruitment tools). The final model was extracted and verified through interviewing the experts and the coding process. The cultural components of each dimension are also extracted and clustered according to the experimental data and according to the experts in a 4-step Delphi process. Finally, the current and desired status of the elite recruitment system in educational organizations has been studied using the gap analysis method. Ten companies were selected as sample for the selection of the community by cluster sampling and the questionnaires were distributed among managers and their human resources experts. The GAMS software is used to analyze the data and determine the effectiveness of the coding model. Effectiveness in the current paper is to determine the optimal value of the dimensions.Findings: Based on the findings, the optimum model dimensions (competency definition, effective factors analysis, competitor’s analysis, and recruitment tools) have increased in optimal condition compared to the current situation. One of the most important reasons for this is the existence of cultural barriers to the recruitment process, which impedes the effectiveness of the process and chooses the right and proper. Removing these barriers is one of the essential requirements for optimizing the proposed model.Conclusion: The results showed that there is a significant difference between the current situation and the desired level, which necessitates serious attention to the factors affecting the elite’s recruitment and the development of appropriate mechanisms for their recruitment in educational organizations.